2016
DOI: 10.1038/srep20695
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogenetic analysis and transcriptional profiling of MADS-box gene family identified DAM and FLC-like genes in apple (Malusx domestica)

Abstract: The MADS-box transcription factors play essential roles in various processes of plant growth and development. In the present study, phylogenetic analysis of 142 apple MADS-box proteins with that of other dicotyledonous species identified six putative Dormancy-Associated MADS-box (DAM) and four putative Flowering Locus C-like (FLC-like) proteins. In order to study the expression of apple MADS-box genes, RNA-seq analysis of 3 apical and 5 spur bud stages during dormancy, 6 flower stages and 7 fruit development s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 60 publications
6
80
3
Order By: Relevance
“…Further interrogation of ‘Royal Gala’ transcripts identified partial sequences that were highly similar to previously reported MdDAMa / MdDAM1, MdDAMc / MdDAM2 and MdSVPb / MdDAM3 / MdJb sequences (Mimida et al, 2015; Nakano et al, 2015; Wisniewski et al, 2015; Porto et al, 2016). Amplification of full-length sequences from ‘Royal Gala’ tissues confirmed that the ‘Royal Gala’ sequences were identical or almost identical to previous reports.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Further interrogation of ‘Royal Gala’ transcripts identified partial sequences that were highly similar to previously reported MdDAMa / MdDAM1, MdDAMc / MdDAM2 and MdSVPb / MdDAM3 / MdJb sequences (Mimida et al, 2015; Nakano et al, 2015; Wisniewski et al, 2015; Porto et al, 2016). Amplification of full-length sequences from ‘Royal Gala’ tissues confirmed that the ‘Royal Gala’ sequences were identical or almost identical to previous reports.…”
Section: Resultssupporting
confidence: 83%
“…Amplification of full-length sequences from ‘Royal Gala’ tissues confirmed that the ‘Royal Gala’ sequences were identical or almost identical to previous reports. However, we could not identify a ‘Royal Gala’ MdDAMd / MdDAM3 , already suggested to be either a pseudogene or a result of misannotation (Mimida et al, 2015; Porto et al, 2016), nor MdDAM4 (KT582789) (Porto et al, 2016). To prevent confusion, the nomenclature proposed by Mimida et al (2015) was chosen (Supplementary Table S2) to reflect the relationship to DAM and true SVP homologs.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations